Studi Pendahuluan Variasi Suhu Permukaan Laut dan Sebaran Aerosol di Laut Sawu - Wicaksono, Ashari; Nuzula, Nike Ika (Program Studi Ilmu Kelautan, Jurusan Perikanan dan Ilmu Kelautan, Fakultas Pertanian, Universitas Mataram, 2021)
Research related to aerosols in Indonesia is still very minimal compared to sea surface temperature parameters and other oceanographic parameters. This study is a preliminary study that aims to determine the variation in aerosol distribution and its influence by variations in sea surface temperatures in the areas crossed by Arlindo, especially the savu sea. Savu sea surrounded by Flores islands (Sumba Regency, Kupang Regency, and Manggarai Regency) has a variation of SPL from 22 - 30 °C, where in the wetar strait, ombai strait, and sumba strait in the northwest part of sawu often occur low temperatures. While the value of aerosol spread is ranging from 0 - 0.3. Thus, a numerical model is needed that can help in analyzing the results that currently exist.